Bioaccumulation of Some Trace elements in muscles of two species of fishes inEuphrates River near the center of Suq Al-Shouyukh city- south Iraq - T. Farhood, Afaq (University of Thi-Qar Journal of Science, 2015)
The present study involved the estimation of the concentration of four trace elements (cadmium ,copper, lead and zinic) in muscles of two species of fishes Barbus luteus and Liza aba collected from the Euphrates river nearSuq-Al-Shouyokh city center south of Iraq, during the period winter and summer 2014 , as an indicator forBioaccumulation of some trace element into tropic level in the aquatic system :water – sediment – fishes , to statement bioaccumulation and biosedimentation of this elements. Also sediment texture and total organic carbon (TOC%) were measured. Analysis employing a flam Atomic Absorption Spectrophotometers .The trace elements were studjed in dissolved and particulate phase of water , in sediment and muscle of this fish ,and recorded bioaccumulation factor (BAF) and biosedimentation factor (BSF) to element above :( 2100-1750 ); (1454 1090);(2172-1830);(1738-1571) respectively concentration as much once in the water, and (0.5-0.42);(0.480.35);(0.58-0.84);(0.21-0.19) respectively concentration as much once in the sediment . The statistical analysis didn't show a significant correlation between most element in sediment and total organic carbon as well as sediment texture .In conclusion the present study , trace elements concentration in particulate phase was higher than their concentrations in the dissolved phase , sediment and muscles of fish , The order of trace element as follows:particulate phase < sediment < fishes muscles (Barbus luteus and Liza aba )<dissolve phase and also the trace elements in the follow order : Zn < Pb < Cu < Cd .